A verification of correlation between chemical monitoring and multi-biomarker approach using clam Ruditapes philippinarum and scallop Chlamys farreri to assess the impact of pollution in Shandong coastal area of China. (June 2020) - Li, Zeyuan; Pan, Luqing; Guo, Ruiming; Cao, Yunhao; Sun, Jiawei
Abstract: Biogeochemical monitoring coupled with multi-biomarker approach were performed for the assessment of marine environment, using clam Ruditapes philippinarum and scallop Chlamys farreri to indicate contamination status in sediments and seawater respectively. The bivalves were collected from three stations, Jiaozhou Bay, Rushan Bay and Laizhou Bay, of Shandong coastal area. A series of contaminants (PAHs and TBBPA) and biomarkers (AhR, EROD, GST, SOD, GPx, CAT, DNA damage) were measured. Multi-biomarker pollution index (MPI) and integrated biomarker response (IBR) were carried out to evaluate contamination status and both indexes showed that Rushan Bay was most polluted, where the pollution level of sediments reached "highly polluted" in August, followed by Jiaozhou Bay and Rushan Bay which reached "lightly polluted". The correlation of IBR values with contaminants' concentrations was verified through the Pearson correlation coefficient ( p  < 0.05), consolidating this scientific assessment method for marine environment. Highlights: MPI and IBR both showed that Rushan Bay was most polluted. Seasonal variation in bivalves was found and attributed to reproduction. The correlation of IBR with contaminants' concentrations was verified ( p  < 0.05).